Cotas para mulheres no legislativo e seus fundamentos republicaons - Maria Aparecida Azevedo Abreu (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The debate about sex quotas in Legislative Power has been developed from a liberal referential. The aim of this Discussion Text is to add new arguments, but from a republican perspective. With these arguments, the discussion about women's rights and interests is displaced by the vindication of their exercising of liberty to be representatives. In view of this, the text defends the State legitimacy for purposing laws to confront the obstacles faced by women due to the masculine domination over them.
Keywords: I30; 330